TAXONOMIC CHANCES AND NEW DISTRIBUTIONAL DATA OF CLERIDAE (INSECTA: COLEOPTERA) FROM ARGENTINE (Acta Entomológica Chilena, 2022)
Neotenerus longicollis Pie, 1935 is recognized as a júnior synonym of Pelonium fossipenne Schenkling, 1917, which is assigned to Riotenerus Pie, 1935, which is elevated to generic status. Following Barr (in litt.), Galeruclerus wagneri Pie, 1933 is synonymized with Pyticeropsis bruchi Schenkling, 1916 and the genus Pelonium Spinola, 1844 is recognized as a valid taxon different from Corinthiscus Fairmaire and Germain, 1861. The following species are cited for the first time for Argentine: Epiphloeusbalteatus Chevrolat, 1843, Pelonium fugax Klug, 1842 and Pelonium scoparius Klug, 1842.
Keywords: Coleóptera, Cleridae, Argentine, Taxonomy, Distribution